Bifidobacterium Longum: Protection against Inflammatory Bowel Disease - Shunyu Yao; Zixi Zhao; Weijun Wang; Xiaolu Liu (Journal of Immunology Research)
The prevalence of inflammatory bowel disease (IBD), which includes ulcerative colitis (UC) and Crohn’s disease (CD), increases gradually worldwide in the past decades. IBD is generally associated with the change of the immune system and gut microbiota, and the conventional treatments usually result in some side effects. Bifidobacterium longum, as colonizing bacteria in the intestine, has been demonstrated to be capable of relieving colitis in mice and can be employed as an alternative or auxiliary way for treating IBD. Here, the mechanisms of the Bifidobacterium longum in the treatment of IBD were summarized based on previous cell and animal studies and clinical trials testing bacterial therapies. This review will be served as a basis for future research on IBD treatment.